Osteosarcoma with Pulmonary Metastasis in a German Shepherd Dog - Betala, Baby Manasa; Kodali, Nagesh Babu; Paidi, Mohini Kumari; Maddireddy, Himaja; Lam, Ratnakumari; Rednam, Amarendhra Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Osteosarcoma is the most common bone tumor in the dogs with highest incidence among bone neoplasms  and exhibits aggressive behaviour characterized by both  local invasiveness and distant metastases (Cavalcanti et al.,  2004; Withrow and Vail, 2007). Osteosarcoma can arise in  any bone of appendicular skeleton, in the following order  of frequency: humerus, radius, ulna, femur, and tibia (Liu  et al., 1977). Osteosarcoma is a highly metastatic neoplasia,  mainly towards the lungs, with 90% of the animals developing  metastases within one year after limb amputation (Brodey  and Riser, 1969). Some breeds like Doberman Pinscher, Saint  Bernard, German Shepherd, Golden Retriever, Great Dane  and Irish Setter are described as having an increased risk  of developing osteosarcoma (McNeill et al., 2007; Morello  et al., 2010). The present paper describes appendicular  osteosarcoma with metastasis of lungs in 12 year old German  shepherd dog.
Keywords: invasiveness; Osteosarcoma; metastases